Embedded systems. real-time interfacing to ARM® Cortex(TM)-M microcontrollers - Valvano, Jonathan W. 1953- (Jonathan W. Valvano, 2014)
This book, published August 2016 as a fifth edition 3rd printing, is the second in a series of three books that teach the fundamentals of embedded systems as applied to ARM Cortex-M microcontrollers. The three books are primarily written for undergraduate electrical and computer engineering students. They could also be used for professionals learning the ARM platform. The first book Embedded Systems: Introduction to ARM Cortex-M Microcontrollers is an introduction to computers and interfacing focusing on assembly language and C programming. This second book focuses on interfacing and system-level design. The third book Embedded Systems: Real-Time Operating Systems for ARM Cortex-M Microcontrollers is an advanced book focusing on operating systems, high-speed interfacing, control systems, and robotics. An embedded system is a system that performs a specific task and has a computer embedded inside. Topics include design, verification, hardware/software synchronization, interfacing devices to the computer, timing diagrams, real-time systems, data collection and processing, motor control, analog and digital filters, real-time signal processing, low-power design, and the internet of things. In general, the area of embedded systems is an important and growing discipline within electrical and computer engineering.